(untitled) - David Brazil (Oxford, 1995)
Using authentic, naturally-occurating data, this book provides an innovative anlysis of the grammar of spoken English. It proceeds from an understanding that speakers and listeners bring to every piece of purposeful discourse a complex bacground of shared understandings which inform their interaction.
Keywords: english language - grammar,english language - study and teaching,english language - textbooks for foreign speakers,oral communication,public speaking,speech - study and teaching